1996
DOI: 10.2527/1996.7471612x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-carnitine and soybean oil on growth performance and body composition of early-weaned pigs.

Abstract: Two experiments were conducted to evaluate the effect of dietary L-carnitine on growth performance and body composition of early-weaned pigs. In Exp. 1, 120 weanling pigs (initially 5.6 kg and 19 +/- 2 d of age) were allotted in a 3 x 2 factorial with four pigs per pen and five replications (pens) per treatment. Main effects from d 0 to 14 after weaning included dietary L-carnitine (0, 500, or 1,000 ppm) and soybean oil (0 to 10%). From d 14 to 35 after weaning, levels were reduced to 0, 250, or 500 ppm L-carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
78
5
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 22 publications
10
78
5
7
Order By: Relevance
“…However, the intensified utilization of fatty acids is not always reflected by decreased NEFA levels. The NEFA concentrations were not affected by carnitine in our previous study (Lö sel et al, 2009) and in carnitine-supplemented weanling pigs (Owen et al, 1996). In contrast, in gestating sows NEFA concentration was decreased by carnitine (Woodworth et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, the intensified utilization of fatty acids is not always reflected by decreased NEFA levels. The NEFA concentrations were not affected by carnitine in our previous study (Lö sel et al, 2009) and in carnitine-supplemented weanling pigs (Owen et al, 1996). In contrast, in gestating sows NEFA concentration was decreased by carnitine (Woodworth et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…Owing to its essential role for the transportation of long-chain fatty acids into the mitochondrial matrix where b-oxidation of activated fatty acids takes place, carnitine is often associated with increased fatty acid utilization as shown in porcine mitochondria in vitro (Heo et al, 2000) and in liver mitochondria and hepatocytes of carnitine-supplemented growing pigs (Owen et al, 2001). As a result, reduced body fat accretion has been observed in suckling, weaning and growing pigs in response to carnitine (Owen et al, 1996 and2001;Lö sel et al, 2009). However, the intensified utilization of fatty acids is not always reflected by decreased NEFA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that inclusion of dietary L-carnitine could enhance the growth performance of starter pigs (Weeden et al, 1990;Owen et al, 1996;Cho et al, 1999a,b). Furthermore, L-carnitine could improve N digestibility, N retention rate as well as biological value of feeds in pigs (Heo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (1994) reported that finishing pigs (34 to 102 kg) fed carnitine had larger LM area and greater percentage muscle than control pigs, but growth performance was not affected. Owen et al (1996) also concluded dietary L-carnitine reduces lipid accretion in early-weaned pigs. Owen et al (2001a) explained the mechanism for these improved carcass characteristics.…”
mentioning
confidence: 99%
“…Carnitine is a vitamin-like compound that facilitates transport of long-chain fatty acids into the mitochondria for adenosine triphosphate production via β-oxidation and oxidative phosphorylation (Owen et al 1996). Smith et al (1994) reported that finishing pigs (34 to 102 kg) fed carnitine had larger LM area and greater percentage muscle than control pigs, but growth performance was not affected.…”
mentioning
confidence: 99%